2019
DOI: 10.1002/aocs.12188
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Saturated and Unsaturated Phosphatidylcholine in Mineral and Vegetable Oils

Abstract: We studied the molecular self-assembly of commercial and pure-saturated and pure-unsaturated phosphatidylcholine (PtdCho) in vegetable (VO) and mineral (MO) oils. The PtdCho self-assembly was monitored through rheology, differential scanning calorimtery (DSC), and polarized light microscopy. The results showed that in the presence of just the constituent water, the PtdCho selfassembly occurred through the formation of a "liquid structure" stabilized by electrostatic interactions. The DSC measurements did not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Consequently, in gelled systems (i.e., oleogels) where G ′ > G ′′ the δ values would be lower than 45 • and the smaller the δ value the larger the gel's elasticity. The use of δ sweeps as a function of ω was particularly useful because allows the study of viscoelastic changes occurring as a function of a timescale in complex systems like crystallization of triglycerides or phosphatidylcholine in vegetable or mineral oil (Toro-Vazquez et al, 2005;Martínez-Ávila et al, 2019). Within this context, in solid-like materials δ would have values lower than 45 • with a rheological behavior nearly independent of δ (i.e., true gels).…”
Section: Relationship Between the Rheology And Microstructure Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, in gelled systems (i.e., oleogels) where G ′ > G ′′ the δ values would be lower than 45 • and the smaller the δ value the larger the gel's elasticity. The use of δ sweeps as a function of ω was particularly useful because allows the study of viscoelastic changes occurring as a function of a timescale in complex systems like crystallization of triglycerides or phosphatidylcholine in vegetable or mineral oil (Toro-Vazquez et al, 2005;Martínez-Ávila et al, 2019). Within this context, in solid-like materials δ would have values lower than 45 • with a rheological behavior nearly independent of δ (i.e., true gels).…”
Section: Relationship Between the Rheology And Microstructure Of The mentioning
confidence: 99%
“…Several molecules of low molecular weight (<3,000 Da) at temperatures below their solubility limit in an organic solvent (i.e., vegetable oil), have the capability of self-assembly. Through this process lipophilic or amphiphilic molecules like phytosterols (Bot and Agterof, 2006;Bot et al, 2008Bot et al, , 2009, lecithin (Han et al, 2014;Martínez-Ávila et al, 2019), monoglycerides (Chen et al, 2009;López-Martínez et al, 2014), (R)-12-hydroxystearic acid (Rogers and Marangoni, 2008;Lam and Rogers, 2011;Abraham et al, 2012;Co and Marangoni, 2013), n-alkanes, long chain alkyl esters, fatty acids and fatty alcohols (Gandolfo et al, 2004;Morales-Rueda et al, 2009;Lam and Rogers, 2011;Co and Marangoni, 2013;Sagiri et al, 2015) form three-dimensional crystal structures that physically trap vegetable oils providing them with viscoelastic and thermoreversible properties (Toro-Vazquez and Pérez-Martínez, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oleogelation can be achieved by initially dissolving a gelator by heating it in the organic solvent and then cooling the solution to a temperature below the solubility limit of the gelator. Under this condition, gelators such as n-alkanes [14], monoglycerides [15], 12-hydroxystearic acid [16,17], some amides [18], lecithin [19,20] and some plant waxes (e.g., candelilla wax, rice bran wax and carnauba wax) [21][22][23][24] go through spontaneous molecular assembly in vegetable oils and mineral oil [20,[25][26][27][28]. Different studies have shown that oleogels are a viable alternative for saturated and trans fat substitution in food products [23,[29][30][31][32] and cosmetic uses [33,34], and recently, they have been used for the controlled supply of substances such as minerals and pharmaceutical products, thus achieving a fluid exchange capacity with the environment [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…To prepare the MG controls, the dispersion of MG in the VO or the MO (20 ml in the glass vials) was placed for 20 min in an oven at 90 C with intermittent gentle stirring, left for 60 min at room temperature and then stored at 15 C. To limit the MG isomerization during the preparation of the MG controls avoided the use of temperatures above 90 C (Lutton, 1971). The preparation of the LC controls were based on the results of Martínez-Ávila et al (2019). Thus, to achieve complete solubilization of LC in the oils, the 2% and 4% LC controls were heated at 120 C and 150 C for 15 min, respectively, left for 60 min at room temperature and then stored at 15 C. After 24 h at 15 C the vials with the MG-LC systems and the MG and LC controls were inverted for 1 h at room temperature (≈20 C) and their corresponding flowing behavior and/or phase separation registered.…”
Section: Ghmentioning
confidence: 99%
“…However, most studies that evaluate the oleogels' formation and their physical properties have been done with vegetable oils. Limited studies have addressed the self‐assembly process of gelator molecules in mineral oil (Aguilar‐Zárate et al, 2019; Bonam, 2013; Martínez‐Ávila et al, 2019). Vegetable oils are mainly composed by triacylglycerides (95%–98%) and some minor components like mono‐, di‐acylglycerides, and free fatty acids.…”
Section: Introductionmentioning
confidence: 99%